Culturally and trauma-informed music therapy: approaches for school settings illustrated through descriptive cases from Norway, the United States and South Africa - Murphy, Kathleen M.; Krüger, Viggo; Stuart-Röhm, Karyn; Thorn, Colton; Berry, Sarah (Frontiers in Psychiatry, 2026)
IntroductionMusic-based wellness programs have emerged as promising approaches for supporting youth development and psychosocial wellbeing in school settings, particularly for adolescents exposed to trauma. This paper examines how music therapy and music-based wellness initiatives can promote emotional expression, identity formation, and peer connection across diverse sociocultural contexts.MethodsWe constructed three case examples drawn from observational data collected in school- and hospital-based wellness programs in Norway, the United States, and South Africa. The cases were analyzed through the lenses of sociocultural learning theory and trauma-informed educational practice to explore how these frameworks informed music-based interventions with adolescents.ResultsAcross all three settings, co-created music experiences facilitated youth voice, emotional expression, and social connection. Collaborative, trauma-informed approaches minimized power differentials between therapists and students, fostering environments of safety, trust, and cultural responsiveness. These conditions supported student empowerment and agency, despite differing structural and sociocultural challenges across contexts.DiscussionThe findings align with existing research on music therapy with trauma-exposed youth, highlighting the importance of co-creation, collaboration, and culturally responsive practice. Music-based wellness programs grounded in sociocultural and trauma-informed frameworks may offer accessible and effective supports for adolescents in school settings. Further research is needed to examine strategies for integrating music therapy and music-based wellness initiatives into school systems to expand access and sustainability.